1991
DOI: 10.1007/bf00375400
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic relations and the propagation of phase boundaries in solids

Abstract: This paper investigates the dynamics of phase transformations in elastic bars. The specific issue studied is the compatibility of the field equations and jump conditions of the one-dimensional theory of such bars with two additional constitutive requirements: the first

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
349
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(360 citation statements)
references
References 38 publications
4
349
0
Order By: Relevance
“…Nonclassical solutions have the distinctive feature of being dynamically driven by small-scale effects such as diffusion, dispersion, and other high-order phenomena. Their selection requires an additional jump relation, called a kinetic relation, and introduced in the context of phase transition dynamics by Slemrod [35,36,13], Truskinovsky [37,38], Abeyaratne and Knowles [1,2], LeFloch [23], and Shearer [33,34], and developed in the more general context of nonlinear hyperbolic systems of conservation laws by LeFloch and collaborators [15]- [17], [3]- [5], [28]- [30], and [27]. See [24] for a review.…”
Section: State Of the Artmentioning
confidence: 99%
“…Nonclassical solutions have the distinctive feature of being dynamically driven by small-scale effects such as diffusion, dispersion, and other high-order phenomena. Their selection requires an additional jump relation, called a kinetic relation, and introduced in the context of phase transition dynamics by Slemrod [35,36,13], Truskinovsky [37,38], Abeyaratne and Knowles [1,2], LeFloch [23], and Shearer [33,34], and developed in the more general context of nonlinear hyperbolic systems of conservation laws by LeFloch and collaborators [15]- [17], [3]- [5], [28]- [30], and [27]. See [24] for a review.…”
Section: State Of the Artmentioning
confidence: 99%
“…The problem of the velocity of the phase-transition front is well understood and extensively discussed in the case of displacive martensitic transformations in solids [6]- [10]. It is shown that the conventional theory, when supplemented by the appropriate kinetic relation, does indeed lead to a well-posed problem.…”
Section: Discussionmentioning
confidence: 99%
“…The notion of a kinetic relation is introduced by Abeyaratne and Knowles [6] following ideas from materials science. They have demonstrated its applicability in the thermoelastic setting and impact problems [7]- [9].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the velocity V depends only on the ends states through the thermodynamic driving force defined by the end states γ ± [17]. Further resulting kinetic relation V(f ) is monotone, passes smoothly through the origin and takes values only in the first and third quadrants (i.e.…”
Section: (C) Homogeneous Materialsmentioning
confidence: 99%